2009
DOI: 10.1016/j.jphotobiol.2008.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Two-photon autofluorescence dynamics imaging reveals sensitivity of intracellular NADH concentration and conformation to cell physiology at the single-cell level

Abstract: Reduced nicotinamide adenine dinucleotide, NADH, is a major electron donor in the oxidative phosphorylation and glycolytic pathways in cells. As a result, there has been recent resurgence in employing intrinsic NADH fluorescence as a natural probe for a range of cellular processes that include apoptosis, cancer pathology, and enzyme kinetics. Here, we report on two-photon fluorescence lifetime and polarization imaging of intrinsic NADH in breast cancer (Hs578T) and normal (Hs578Bst) cells for quantitative anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
211
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(229 citation statements)
references
References 71 publications
16
211
2
Order By: Relevance
“…As described previously [19], data were processed using custom designed software developed in Matlab and employing metrics derived from FLIM data as detailed in Vishwasrao et al and Yu et al [13,14]. To characterize the system's instrument response function (IRF) and to aid with data processing, FLIM measurements were recorded of dissolved NADH (0.5 mM in saline) at the beginning or conclusion of each experiment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As described previously [19], data were processed using custom designed software developed in Matlab and employing metrics derived from FLIM data as detailed in Vishwasrao et al and Yu et al [13,14]. To characterize the system's instrument response function (IRF) and to aid with data processing, FLIM measurements were recorded of dissolved NADH (0.5 mM in saline) at the beginning or conclusion of each experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Time-resolved decay profiles of NADH autofluorescence permit distinction of multiple fluorescence lifetime components associated with different 'NADH species,' which reportedly reflect differences in NADH enzymatic binding. Investigators have demonstrated variations in FLIM-based observations of NADH in response to pharmacological and physiological disruptions and disease progression in cell cultures, tissue slices, and in the liver in vivo [13][14][15][16][17][18]. We previously demonstrated in vivo 2PM-based FLIM (2P-FLIM) measurements of cerebral NADH in anesthetized rats, and observed how cerebral NADH fluorescence can be resolved into 4 distinct lifetime components whose amplitudes change rapidly with anoxia and recovery [19].…”
Section: Introductionmentioning
confidence: 99%
“…Because excitation in the 350-450-nm wavelength range is highly toxic to cells, and because shifts in the emission spectra due to molecular interactions in cells make the analysis difficult, this approach of metabolic mapping in living cells and tissues became obsolete. However, the application of dual-photon excitation of NADH at 730 nm, which reduces cytotoxicity considerably, the determination of the ratio of free and protein (enzyme)-bound NADH using fluorescence lifetime imaging microscopy and anisotropy of autofluorescence, and the application of fast photon detection re-introduced NADH as an attractive probe for spatially resolved imaging of the metabolism of living cells (Ramanujam et al 1994;Bird et al 2005;Ramanujan et al 2008;Yu and Heikal 2009). The focus of these studies is particularly on metabolic mapping of normal and malignant cells and tissues.…”
Section: Endogenous Fluorescent Metabolitesmentioning
confidence: 99%
“…The ratio of free/bound NADH varies significantly from 1.5:1 20 to 1:4. 21 For example, Wakita et al 23 were unable to detect free NADH in rat liver mitochondria regardless of their respiratory state, whereas Blinova et al 20 observed a high proportion of free NADH in pig heart mitochondria using a similar technique. Interestingly, Kasimova et al suggested that the free NADH concentration in plant mitochondria is kept constant under different metabolic conditions.…”
mentioning
confidence: 99%
“…15 The mitochondrial NAD + -NADH ratio also varies from 2 to 16 in different reports. [16][17][18] In recent years, an increasing number of studies on free NADH were largely focused on measurements via time-resolved fluorescence, 19,20 fluorescence anisotropy, 21,22 and fluorescence spectral decomposition analysis. 16 These techniques enable researchers to distinguish between the protein-bound and free NADH in the intracellular environment.…”
mentioning
confidence: 99%